Kritik Orientalisme terhadap Al-Quran: Analisis dan Tanggapan Sarjana Muslim - Athar, Mohamad (Fikroh: (Jurnal Studi Islam), 2024)
Abstract Orientalism is the study of the Eastern world by Western scholars, often based on perspectives and analytical methods different from Islamic traditions. One of the main focuses of Orientalism is the Quran, the holy book of Islam. Orientalist criticism of the Quran encompasses various aspects, such as the authenticity of revelation, the use of foreign vocabulary, borrowing theories and influences from other religions, and inconsistencies in writing. This article explores the main criticisms of Orientalism against the Quran, the responses from Muslim scholars, and the impact of these criticisms on the understanding of the Quran. Using a qualitative approach and literature study method, this research collects and analyzes data from secondary literature, including books, journals, articles, and relevant online sources. The data is then descriptively and analytically examined to understand the detailed criticisms and responses within their historical and intellectual contexts. The study employs source triangulation to ensure data validity and systematically presents the findings in key sections: Orientalist criticisms, Muslim scholars' responses, and the impact of these criticisms on Quranic understanding. This research aims to provide a comprehensive overview of the debate between Orientalists and Muslim scholars regarding the Quran and the implications of this debate for Islamic studies.